Waiting list patient group evolution analyzed through MELD (Model For End-Stage Liver Disease) - Zilberstein , Bruno; Eshkenazy , Rony; Meniconi, Marcos Tulio; Santos Jr, Edílson Duarte dos; Melo , Catia Rejânia Ribeiro; Brasileiro , Fábio Marcondes; Correa , Fabiana (Brazilian Journal of Transplantation, 2005)
The model for hepatic terminal disease (MELD) was developed in 2000 with the intention to predict the mortality rate in patients 90 days after transjugular intrahepatic porto systemic shunt (TIPS). Objective: demonstrate the facility and reliability of MELD application in national SUS waiting list patients, as well as raise the possibility of its uses as legal criteria, aiming to reduce the mortality of the waiting list. Method: Forty three patients inscribed in the unique waiting list for liver transplantation at Hospital Bandeirantes between June 2002 and March 2003 were analyzed. Thirty three male and 10 female, with an average age of 48,7 years old, varying from 20 to 65. Results: The MELD calculated at that moment when patients were inscribed varied from 7 to 39, with an average of 14. Actually, the MELD calculated varied from 6 to 40 with an average of 20. A rate of 6% of mortality was observed in the waiting list. As the Chi square test was applied, p was 0,001, having a significant difference between the MELD calculated at the list inscription and recently, highlighting the reduction in their hepatic function. Conclusion: The analysis based on MELD score shows a worsening situation of the patients’ hepatic function since their inscription in the waiting list, until their transplantation.